Ethiopian energy status and demand scenarios: Prospects to improve energy efficiency and mitigate GHG emissions - Mondal, Md. Hossain Alam; Bryan, Elizabeth; Ringler, Claudia; Mekonnen, Dawit Kelemework; Rosegrant, Mark W. (Elsevier, 2018)
The energy sector of Ethiopia continues to largely rely on traditional biomass energy due to limited access to modern energy sources to meet growing demand. Long-term energy demand forecasting is essential to guide the country's plans to expand the energy supply system. This study provides a general overview of Ethiopia's current energy demand and forecasts sector-wise energy demand out to 2030 for alternative policy scenarios using the Long-range Energy Alternative Planning (LEAP) model. The reference scenario assumes a continuation of recent energy consumption trends and takes account of current energy and economic dynamics. Three alternative scenarios on improved cookstoves, efficient lighting, and universal electrification scenario were identified as key priorities of the government of Ethiopia and modeled. Results from the model can assist energy planners in ensuring that the country's capacity for supply meets projected growth in demand for energy. They also shed light on the tradeoffs implicit in alternative policy priorities and investments in terms of economic development and environmental sustainability. Most importantly, the results suggest that alternative investments can conserve energy, improve environmental sustainability, enhance energy equity and improve the country's development indicators.